Implementation of Islamic Spiritual Extracurricular Activities in Instilling Character Education in Students at SMA Kartika I-2 Medan, Medan Helvetia District - Neliwati; citra, Yulia; Rafika; Al-Hilal Habibi Sihotang (Inspiratif Pendidikan, 2024)
Intra-school organizations that deepen and strengthen students' personalities to become more Islamic is one of the meanings of ROHIS or Rohani Islam. Rohis is usually carried out in extracurricular form in middle and high schools. Rohani Islam is a large association owned by students to be able to carry out da'wah activities at school. This Islamic spiritual activity can also shape students' character that reflects the Prophet Muhammad. This research uses one method, namely the qualitative method using a descriptive approach. The analytical method used is a monitoring or observation approach, interviews and documentation studies. This research aims to implement Rohani Islam extracurricular activities in instilling character education in students at SMA Kartika I-2 Medan, Medan Helvetia District.